Analysis of the public policy on food and nutritional security for Bogotá "Building Food Citizenship 2019-2031" (2021)
In this essay, the Public Policy of Food and Nutritional Security for Bogotá "Building Food Citizenship 2019-2031" will be analyzed, highlighting the value it has for the District Government in the search to solve the problem of Food and Nutrition Stability, the development of activities to ensure entry into a balanced and healthy basic food basket, as well as promoting and strengthening good eating habits throughout the population, thus generating true food citizenship, within a sustainable and inclusive supply and distribution system of healthy foods with a regional focus.